Pharmaceutical policies for diseases related to poverty in Brazil: a review (Research, Society and Development, 2021)
The "epidemiological transition" has fostered increasing attention to chronic and non-communicable diseases, but neglected diseases are still present and their relationship with the population's socioeconomic inequalities is increasingly evident, so much so that there has been a conceptual conversion to call them “poverty-related diseases”. It is a necessary to review and to discuss the characteristics and challenges of Brazilian pharmaceutical policies for populations affected by diseases related to poverty. This review of the literature was carried out, with works of the last 10 years dealing with the theme and the Brazilian reality. Out of the 272 identified articles, only 43 publications were included in this study. The results were: (i) the difficulties of investing in the research, development and production of new drugs for these diseases; (ii) the characteristics of access policies to medicines already available, their advances and limitations; (iii) and issues related to the right to comprehensive pharmaceutical assistance. Therefore, for the available therapies, national production and federal funding contributed to guarantee the supply. Assisted qualification actions are necessary and little discussed in area studies.